Germplasm evaluation and identification of the population source of hard clam (Mercenaria mercenaria) in China using SSR and COI markers - Wang, JunYi; Xue, DongXiu; Yang, MeiJie; Ji, YunLong; Song, Hao; Zhou, Cong; Shi, Pu; Li, YongRen; Guo, YongJun; Meng, FanYu; Lai, ChangPing; Cheng, ShunFeng; et al. (Frontiers in Marine Science, 2024)
In aquaculture, good germplasm resources are nearly decisive for its development. The hard clam (Mercenaria mercenaria), a significant marine aquaculture bivalve in China, has flourished quickly since being introduced from North America in 1997. However, for numerous reasons, it has suffered from germplasm deterioration and uncertain origins. To address these issues, seven microsatellite DNA loci (SSRs) and mtCOI were employed to evaluate germplasm and trace the origins of various Chinese populations. The results of these two molecular genetic markers revealed weak genetic differentiation among all Chinese populations, with high genetic diversity observed across most individuals, except for a few outliers. This suggests an alarming situation regarding germplasm resources in China. Based on results of traceability analysis, the most likely areas of origin for the Chinese populations are Chesapeake Bay and the southern region of Cape Hatteras. This study provides a crucial theoretical foundation for the cultivation, conservation, and subsequent introduction of hard clam populations in China, thereby ensuring the sustainable growth of the hard clam breeding sector.